Branding a family business - Pohjola, Matti (2016)
This master’s thesis main object was to understand better the very little researched topic: branding a family business. The main aim was to seek the values used behind family business that are the family values used in the brand and how the branding has been implemented in a family company. A qualitative method was chosen for this research for an interpretative analysis of the subject. Five family companies were chosen for the interviews. All these family companies are known Finnish companies which have a great brand and can be defined as true family businesses from their ownership and governance. Before the interview, all interviewees were given a questionnaire which was formulated based on the theory part of the thesis. The results from the research give us interesting points from the family business branding, family values and the branding strategy. There are also guidelines and advice given from the interpretation of the results. The results also give a good base for the future research in this pioneering work of branding a family business.